أحكام العدول عن الخطبة وتطبيقاتها في المحكمة الشرعية بولاية كوالالمبور الفيدرالية : دراسة فقهية تحليلية - Nurul 'Arifah Binti Mohamad (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study presents the rules governing giving up of betrothal and their applications in the Federal Territory of Kuala Lumpur Shariah Court. The main purpose of this study is to have a better understanding of betrothal, and the giving up of betrothal, and its maqasid and importance. Additionally the purpose is to explain the rules governing of giving up the betrothal in Islamic jurisprudence and the applications in the Federal Territory of Kuala Lumpur Shariah Court, and explain the court processes and procedures in handling such cases. The research methods that were employed by the researcher were the descriptive, analysis and interview methods. The interviews were held at Federal Territory of Kuala Lumpur Shariah Court and the respondents are shariah judges and the assistant registrar. The importance of the study is to act as a reference for students and researchers in helping them to have a better understanding about the applications of the rules governing giving up of the betrothal in Federal Territory of Kuala Lumpur Shariah Court. At the same time this research will help the Federal Territory of Kuala Lumpur Shariah Court to deal with matters and cases related with the rules governing giving up of the betrothal from the view of Islamic jurisprudence. Besides this, this research proposes a better solution in dealing with these cases. It is also worth mentioning that among the importance of this research is to correct the understanding among Muslims about the betrothal and the giving up of the betrothal by explaining the rules and the wisdom behind legitimising both. The findings show that betrothal is a non-binding contract and the giving up of the betrothal is allowed by the Islamic jurisprudence with the permissible reason justified by the shariah. Additionally, the Federal Territory of Kuala Lumpur Shariah Court allows claiming the compensation of Dharar and Harm as the effect and consequence of the giving up of the betrothal, and it is also worth mentioning that the application in the shariah court related with the issue of claiming the betrothal gifts is supported by the Maliki school of thought.